TREND ANALYSIS OF AVERAGE TEMPERATURE AND PRECIPITATION DATA OF AKARCAY CLOSED BASIN (AFYONKARAHISAR-TURKEY) - Sevda Coşkun (Fırat University, 2020)
The extent of the present study comprises the Akarçay closed basin located within the border of the provinces of Afyonkarahisar and Konya. The present study is aimed to perform trend analysis of average temperature and total precipitation of three meteorological stations (Afyonkarahisar, Bolvadin ve Akşehir) with more than 30 years of observation (1970-2019) in the basin. Besides, the aim of the study is also to analyze the annual and seasonals trends of these data by considering the monthly measured average temperature and total precipitation data of meteorological observed over many years across the basin. The study will also contribute to the national and international literature on climate change studies with another example from Turkey. The research method is based on the Mann-Kendall Test and Spearman's Rho Test. The results showed significant increases in mean temperatures throughout the closed basin, both annually and seasonally. In the Akarçay Basin, summer is the season where the positive trend seen in temperature is strongest. In addition to increasing electricity consumption in the region because of the cooling requirement, this situation can also encourage the production of solar energy from renewable energy sources. Strong positive significant trends in summer temperatures in the akarçay basin can increase the frequency of wildfires and risk dry forests in the basin. As annual rainfall, Bolvadin increases significantly in stations, while Akşehir decreases significantly. There is no significant increase or decrease in Afyonkarahisar. It is understood that the temperature increases observed across the watershed do not have a significant effect on rainfall.